2020
DOI: 10.1038/s41598-020-71350-x
|View full text |Cite
|
Sign up to set email alerts
|

An approach for the measurement of the bulk temperature of single crystal diamond using an X-ray free electron laser

Abstract: We present a method to determine the bulk temperature of a single crystal diamond sample at an X-Ray free electron laser using inelastic X-ray scattering. The experiment was performed at the high energy density instrument at the European XFEL GmbH, Germany. The technique, based on inelastic X-ray scattering and the principle of detailed balance, was demonstrated to give accurate temperature measurements, within 8% for both room temperature diamond and heated diamond to 500 K. Here, the temperature was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The elastic scattering of hard x-rays can be estimated with a delta function in this work, since x-ray scattering from phonons is on the order of 100 meV. 51 Therefore, the peak shape at 6 keV of the elastic scattering signal, presented in Fig. 3 (left), can serve as a good approximation of the instrument function, which describes the broadening of the signal due to beamline and spectrometer contributions.…”
Section: Resultsmentioning
confidence: 99%
“…The elastic scattering of hard x-rays can be estimated with a delta function in this work, since x-ray scattering from phonons is on the order of 100 meV. 51 Therefore, the peak shape at 6 keV of the elastic scattering signal, presented in Fig. 3 (left), can serve as a good approximation of the instrument function, which describes the broadening of the signal due to beamline and spectrometer contributions.…”
Section: Resultsmentioning
confidence: 99%
“…These physical effects are interesting in their own right, and the required perturbation amplitudes can be realized in experimental facilities. We also show that the energy resolution of present experiments 85 is sufficient to resolve the emerging modes and features.…”
Section: Discussionmentioning
confidence: 54%
“…Importantly, this example is as an illustration and, in general, other (smaller) values of the wave numbers can be probed. We note that recently an energy resolution better than for diagnostics using inelastic X-ray scattering at the high energy density instrument of the European XFEL has been reported 85 . This enables probing various new features in the electronic excitation spectrum discussed in this work.…”
Section: Experimental Feasibilitymentioning
confidence: 84%
“…We observed the hardening of phonon spectra in the solid regime of the Hugoniot compression and, analogously, studied the shift of ion acoustic modes to higher excitation energies. Phonon hardening is currently lively debated and recent work has shown that phonons can be resolved at free electron laser facilities [17][18][19], enabling future direct observations of phonon hardening in shock compression experiments. We found the adiabatic speed of sound along the Hugoniot to be slightly underestimated by DFT-MD relative to recent experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…[16]. With novel improvements to the spectral resolution at X-ray free electron laser facilities, it is now becoming possible to measure the ion-ion DSF of transient WDM states [17][18][19]. This allows us to probe the ion dynamics of dynamically compressed targets, requiring sophisticated many-body simulations, that take into account the quantum mechanical nature of WDM states, to compare with the experimental observations.…”
Section: Introductionmentioning
confidence: 99%